TESTING THE C4.5 ALGORITHM WITH RAPID MINER TO DETERMINE DECISIONS FOR IMPLEMENTING SPORTS ACTIVITIES - Siregar, Kristian (Sean Institute, 2023)
In the current era of information technology, decision making is an important aspect in various fields, including in the world of sports. The decision to carry out sports activities can be influenced by many factors such as weather conditions, availability of facilities, and the physical condition of the participants. With advances in technology and data science, there are algorithms that can assist in making these decisions. One of them is the C4.5 algorithm. This study aims to test the effectiveness of the C4.5 algorithm in determining decisions to carry out sports activities using the Rapid Miner software. The data used in this study is historical data from sports activities which include variables such as weather, date, and condition of the participants. The test results show that the C4. 5 is able to provide decisions with fairly high accuracy. By using Rapid Miner software, the process of learning and testing data becomes faster and more efficient. The conclusion of this study is that the C4.5 algorithm, with the help of Rapid Miner software, can be used as an effective method to assist in making decisions about sports activities.